Human seminal alpha inhibins: isolation, characterization, and structure. - Li, C H (1985)
Two additional peptides with inhibin-like activity have been isolated from human seminal plasma. One consists of 52 amino acids and the other, 92 amino acids. They are designated alpha-inhibin-52 and alpha-inhibin-92. Sequence analyses show that the NH2-terminal 31 amino acids of alpha-inhibin-52 are identical to the structure of the inhibin-like peptide previously reported [ILP-(1-31), now designated alpha-inhibin-31], and the COOH-terminal 52 amino acids of alpha-inhibin-92 are identical to the structure of alpha-inhibin-52. The amino acid sequence of alpha-inhibin-92 is: (sequence in text) Bioassay data in mouse pituitaries in vitro show that alpha-inhibin-52 is 3.4 times more active and alpha-inhibin-92 is greater than 40 times more active than alpha-inhibin-31 in suppressing follitropin-release. Radioimmunoassay data indicate that alpha-inhibin-52 and alpha-inhibin-92 have only 60% immunoreactivity.